1989
DOI: 10.1164/ajrccm/140.6.1693
|View full text |Cite
|
Sign up to set email alerts
|

An Immunohistochemical Study of Architectural Remodeling and Connective Tissue Synthesis in Pulmonary Fibrosis

Abstract: Fibroblasts in healthy adult lung are quiescent, synthesizing little collagen. We studied lung biopsies from 30 patients with pulmonary fibrosis, using immunohistochemistry with monoclonal antibodies against the propeptides of type I collagen to localize fibroblasts actively synthesizing collagen. Adjacent sections were stained with antibodies to type III and IV collagen, fibrin, cytokeratin, plasma fibronectin, or EDIIIa-containing "cellular" fibronectin (cFN). In rapid pulmonary fibrosis, including the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
225
1
6

Year Published

1992
1992
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(243 citation statements)
references
References 14 publications
8
225
1
6
Order By: Relevance
“…This observation is also of considerable interest considering that increased procollagen type III occurs early in pulmonary fibrosis and is thought to be predictive of fibrotic diseases in the lung. 49,70 Although constitutive levels of TGF-␤ did not differ between the two types of fibroblasts, levels of this cytokine were approximately sevenfold higher in cultures of IL-4-stimulated fibroblasts from L-NAME-treated mice compared with their D-NAMEtreated counterparts. Furthermore, in vitro IFN-␥ treatment of fibroblasts from L-NAME-treated mice did not abolish TGF-␤ synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…This observation is also of considerable interest considering that increased procollagen type III occurs early in pulmonary fibrosis and is thought to be predictive of fibrotic diseases in the lung. 49,70 Although constitutive levels of TGF-␤ did not differ between the two types of fibroblasts, levels of this cytokine were approximately sevenfold higher in cultures of IL-4-stimulated fibroblasts from L-NAME-treated mice compared with their D-NAMEtreated counterparts. Furthermore, in vitro IFN-␥ treatment of fibroblasts from L-NAME-treated mice did not abolish TGF-␤ synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…The increase of collagen and other components of extracellular matrix occur as a tissue response to injury and can lead to fibrosis of the organ. Previous studies have demonstrated that collagen synthesis is increased in pulmonary fibrosis (7), in glomerulosclerosis (8) and in other pathologies.…”
Section: Introductionmentioning
confidence: 97%
“…The ECM is a highly dynamic complex that varies in composition according to its tissue localization and physiologic circumstances. Collagens are the predominant ECM proteins identified in fibrotic lesions and are the hallmark of fibroproliferative diseases, but fibronectins (FNs) are also present in abnormally large quantities and localize to areas of active fibrogenesis (3,4).…”
mentioning
confidence: 99%